Selective nickel recovery from spent catalyst - Mat, Hanapi; Y., Yuliusman; Othman, Norasikin (1999)
Nickel recovery from spent nickel catalyst that involved two consecutive steps: (1) extracting the metals from solid spent catalyst using acid leaching, and (2) selective precipitation of nickel from other metals by an addition of sodium hydroxide was studied. In leaching process it was found that sulphuric acid as a leaching resulted significantly higher nickel concentration compared to nitric and hydrochloride acids, and the amount of nickel extracted increases with increasing in acid concentration used. It was also found that the concentration of nickel in spent catalyst is about 8.15% (dry weight). In the selective precipitation, sodium hydroxide was used to adjust the pH of the solution. The results show that nickel starts to precipitate at higher pH probably as (NiOH)2 or 3Ni(S04). 4Ni(OH)2 than A1, Zn, and Fe that is, at the optimum pH, more than 80% of nickel recovery was obtained.